Seismic demands on secondary systems in base-isolated nuclear power plants. - Huang, Yin-Nan (Earthquake engineering & structural dynamics.)
Numerical models of a sample nuclear power plant (NPP) reactor building, both conventionally constructed and equipped with seismic protective systems, are analysed for both safe shutdown and beyond-design-basis earthquake shaking at two coastal sites in the United States. Seismic demands on secondary systems are established for the conventional and seismically isolated NPPs. The reductions in secondary-system acceleration and deformation demands afforded by the isolation systems are identified. Performance spaces are introduced as an alternate method for evaluating demands on secondary systems. The results show that isolation systems greatly reduce both the median and dispersion of seismic demands on secondary systems in NPPs.